Legal Politic of Corruption Eradication After the Prevail of the Amendment Act of Corruption Eradication Commission - Muhamad Rajab Fadli; Evi Vardiyana Kusumawati; Siti Salha Mazaya; Saufi Hidayat; Hariyanto Hariyanto (Unram Law Review, 2022)
The amendment on corruption eradication legal policy after the enacmnet of Act Number 19 Year 2019 Concerning the Amandment of Act Number 30 Year 2002 Concerning Corruption Eradication Commission derived pros and cons among legal expert and activis of anti corruption. This study aims to determine the political policy of corruption eradication after Act Number 19 Year 2019 in force. This research is a doctrinal study and using statute approach and conceptual approach. Result of this study showed that there is considerable change in the corruption eradication act includes: the institution of Corrution Eradication Commission subsumed as part of executive institution, internal supervision under Supervision Board, transformation of Corruption Eradication Commission employe become State Civil Servant. In addition, there are numerous augmentations on the duty and fuction of the Commission. Those changes impacted to the internal body of Corruption Eradication Commission, particularly toward its independence.